Differences in Factors that Limit School Efforts to Provide Mental Health Services by School Level: A National Analysis - Chastity Harper Simon; John R. Slate; Cynthia Martinez-Garcia (Journal of Research in Education and Pedagogy, 2025)
The degree to which factors limited the efforts of school leaders to provide mental health services to their students was addressed in this multiyear investigation. We analyzed national data from the National School Survey on Crime and Safety for the 2015-2016 and 2017-2018 school years. A causal-comparative research design was used because of the use of pre-existing data. In this survey, school principals and/or designees were asked about numerous school programs, student achievement, and student demographic characteristics. We analyzed only those survey questions directly related to providing mental health services. Inferential statistical procedures revealed the presence of statistically significant differences in a lack of access to mental health professionals and a lack of community support for both school years. Elementary schools had a higher percentage of effort limited in a major way by a lack of access to mental health professionals and community support than did middle or high schools. Additionally, elementary schools had the highest percentage limited in a major way for: lack of parental support, concerns about reactions from parents, reluctance to label students, and payment policies. Implications for policy and practice were discussed, as well as recommendations for further study.